Humanization through touch: a qualitative research with workshops - Maria Cidney da Silva Soares; Chirlaine Cristine Gonçalves; Hudson Pires de Oliveira Santos Junior; Maria de Fátima de Araújo Silveira (Online Brazilian Journal of Nursing, 2009)
<!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> With a view to identifying new knowledge on nursing care that will give additional support to nurses, this qualitative study sets out how final year nursing students conceive of the meaning and value of touch as a therapeutic instrument. Data was gathered from workshops on awareness-raising, expressiveness and creativity; through participative observation; and from field diary records. 13 final year nursing students at the State University of Paraíba, Campina Grande-PB took part. The findings, based on statements taken, emphasize touch as a fundamental strategy for humanization, which makes it viable to have an empathic relationship between client and professional. Professionals must display the sensitivity needed to use touch appropriately and at appropriate times. Therefore, the act of touch needs to be understood beyond its physical aspect, because this involves subjective factors, both by those who do the touching and those being touched. The workshops were successful in reawakening a sense of humanization, which had apparently lain dormant amongst group participants. They now regard touch as a means to establish a relationship of exchange, reward and respect between nurse and client, which is indispensable in the caregiver’s daily routine.